A critical librarianship approach for teaching patent searching: Who becomes an inventor in America?. Issue 1 (3rd April 2021) - Zwicky, David; Stonebraker, Ilana
Abstract: The ways in which a technology is invented, owned, and approved are strongly influenced by the same oppressive and exclusionary structures that critical librarianship interrogates. Patents, limited-term grants of rights to inventions, are issued to inventors in exchange for detailed specifications of the invention. This paper examines current practices used by business librarians in teaching students how find patents and how these practices could be critically informed given the nature of the United States patent system as it exists today. An output of this work is a suggested lesson plan with recommended resources.